Comparison of Business Environments in Oil-Rich MENA Countries: A Clustering Analysis of Economic Diversification and Performance - Aker, Sule L.; Aghaei, Iman (Routledge Journals, Taylor & Francis Ltd, 2019)
The purpose of present research is to cluster 11 oil-richest MENA countries; Algeria, Egypt, Iran, Iraq, Kuwait, Libya, Oman, Qatar, Saudi Arabia, Sudan, and the United Arab Emirates regarding economic diversification and performance during 2010-2016 using K-means algorithm which is a versatile data mining technique. The major finding is that higher export diversity in addition to better economic performance can influence competitiveness of business environment of the countries positively and vice versa. The studied nations are partitioned into four clusters. Qatar and UAE with highest economic diversity and performance have the most favorable business environments in the region.
Keywords: Business environment; economic diversification; economic performance; K-means clustering algorithm; MENA countries